Analisis kondisi akses ketersediaan pangan rumah tangga saat pandemi Covid-19 di Kabupaten Malang - Marliana Eka Fauzia; Elfrida Br Silalahi (Universitas Merdeka Malang, 2022)
The discussion of this research is about the food availability of Malang Regency families during the Covid-19 pandemic. Food security is a crucial issue during the Covid-19 pandemic because it involves affordability of food access, considering the government is currently implementing social restrictions in various regions in Indonesia. The purpose of this study is to analyze changes in access to food availability for the people of Malang Regency in meeting the food needs of the family. As an analytical knife, the researcher uses a literature review regarding access to food availability and literacy regarding the impact of COVID-19 on food. The method used is qualitative with a phenomenological approach. The results of this study indicate that the Malang Regency Government provides direct access and also social access in assisting households in accessing food needs. By ensuring food stability, providing nutrition for vulnerable people/groups and reviewing trade taxes.